More than a warning: Expanding the role of communication in Eastern Caribbean volcano science - Graham, Omari; Edwards, Stacey; Robertson, Richard (Frontiers in Earth Science, 2022)
The infrequent nature of volcanic eruptions means that civil authorities and the public may often be unfamiliar with volcanic hazards and may not be fully prepared to deal with them. Many times volcano scientists are required to help governments and citizens understand the threat posed to their lives and property when volcanoes show signs of an imminent eruption. Effectively communicating the potential impact of these events can demand time and skills that these scientists may or may not have. Further, a lack of trusted scientific information can lead to public misinformation and hamper government responses. Although several risk reduction researchers and observatory scientists have advocated for the inclusion of communication specialists in scientific teams, communication resources at many observatories remain under utilised. Using the experience of The University of the West Indies Seismic Research Centre (UWI-SRC), this article explores the contribution of a specialist communication team to the work of a volcano monitoring agency. The Education and Outreach (E&O) team at the UWI-SRC manages all the agency’s external communications. The team also works to raise public awareness of geological hazards in the UWI-SRC’s Eastern Caribbean region of responsibility. Within the Caribbean region, most communication research related to disaster risk up until now has focused on communication during crises. Using semi-structured interviews and document review we investigated the impact of strategic communication in a long-term, multi-hazard monitoring programme. A qualitative analysis highlighted the equal importance of crisis communication during unrest and outreach work during quiescent periods. The UWI-SRC’s communication programme has been effective in: 1) supporting scientists’ public communication 2) sustaining stakeholder engagement 3) building physical and social science capacity and 4) strengthening organisational credibility. This article examines the contribution of specialist communication to advisory volcano science throughout the disaster management cycle in the English-speaking Eastern Caribbean. It argues that significant societal value can be added to the scientific work engaged in by advisory scientists by embracing a multi-level communication strategy.